2014
DOI: 10.1097/iae.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

Gucy2d- Or Guca1a-Related Autosomal Dominant Cone–rod Dystrophy

Abstract: GUCA1A and GUCY2D mutations are both accompanied by similar pattern of generalized cone dysfunction with a tendency to less involvement of the rod photoreceptors and a less severe phenotype in patients with GUCA1A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…3). 13,19 Briefly, the onset of disease occurred between childhood and early adulthood, with a progressive nature. Visual acuity was reduced in all patients.…”
Section: Dominant Familiesmentioning
confidence: 99%
“…3). 13,19 Briefly, the onset of disease occurred between childhood and early adulthood, with a progressive nature. Visual acuity was reduced in all patients.…”
Section: Dominant Familiesmentioning
confidence: 99%
“…A phenotype very similar to the small hypo-AF dots seen in this study can be found in at least some cases of CDHR1 retinal dystrophy as well 23,26. Review of published cases in which autofluorescence (primarily SW-AF) was performed in other genetic forms of CRD (neither PROM1 nor CDHR1 ) showed that, with this imaging modality, a substantial majority did not resemble the cases presented here 12,2633. However, isolated cases of CRD associated with C8orf37 , CERKL , GUCA1A , and RDS mutations did show moderate resemblances to the AF images presented here 3437…”
Section: Discussionmentioning
confidence: 63%
“… 7 The clinical picture of GUCY2D mutations includes cone-predominant retinal dystrophy with glare, color vision, dark adaptation deficits, and neuroepithelial atrophy. 8 Phenotypic characterization in our proband included disturbance of the retinal pigment epithelium, mild enophthalmos, and temporal optic disc pallor.…”
Section: Discussionmentioning
confidence: 97%